THE IDEA OF AN OLD QUR'AN MANUSCRIPT: ON THE COMMERCIALIZATION OF THE INDONESIAN ISLAMIC HERITAGE - Wieringa, Edwin (Center for Research and Development of Religious Literature and Heritage, 2014)
A Qur?an manuscript, now in the possession of the University of Cologne, Germany (call number Cod. Malaiologie 001/2012), can be regarded as a ?fake? in the sense of having a misleading appearance. This manuscript is a fairly recent bricolage which aims to represent the idea of an old Qur?an manuscript, thereby catering to the increased demand on the international market for old manuscripts from insular Southeast Asia.